Usability of the integral asie instructional design model website in instructional planning - Nurul Liyana, Che Ismail (2023)
This research had a great impact on teachers’ instructional planning following the Malaysia Ministry of Education (MOE) policy, which encouraged teachers to fully embrace the use of digital application tools in their instructional planning. The Integral ASIE Instructional Design Model website provides teachers with the competencies needed in particular subjects, which will reduce stress and improve teachers’ professionalism in the 21st Century Learning environment. Since the website is widely used by teachers in the state of Negeri Sembilan, WAMMI (Website Analysis and Measurement Inventory) was selected to evaluate its usability using five dimensions, namely Attractiveness, Controllability, Helpfulness, Efficiency, and Learnability to ensure its effectiveness. The research methodology is based on the Agile Method in constructing the Usability Evaluation Flow (UEF), which consists of five phases, namely Plan, Analyze, Evaluate, Improve, and Reevaluate. The WAMMI questionnaires with a 4-point Likert scale, Strongly Agree, Agree, Disagree, and Strongly Disagree are used. A semi-structured interview with open-ended questions was used to detail the improvements needed to the website. As this study aims to improve the usability of the website, two specific objectives were formulated: (i) to evaluate the profile of each dimension of the WAMMI questionnaires and (ii) to improve the weaknesses of the website for each dimension. At the initial stage, 20 respondents were involved in identifying the website's weaknesses. Then, 100 respondents participated in a 4-day workshop under the supervision of the Port Dickson Education District Office (PPD). This workshop was conducted in conjunction with the model pilot project initiated by the Negeri Sembilan State Education Department. The suggested items for improvement have been sent to the developer, and modifications have been made. During the re-evaluation phase, another 30 respondents from the same sample were selected. There was an increase in the average mean of the website's usability. This study has contributed to the Digitalization in Education initiative outlined in the Malaysia Digital Economy Blueprint (MDEB).